Pengaruh Aksesibilitas Kendaraan Umum Terhadap Perkembangan Perekonomian Lokal Di Kecamatan Winong, Pucakwangi, Jakenan - Moh Luthfi Nurul Afif (Fakultas Teknik Universitas Pasifik Morotai, 2024)
Poor infrastructure conditions, hilly terrain and narrow roads are factors that affect access to the Pucakwangi, Jakenan, Winong sub-district areas. The aim of this research is to determine the level of accessibility of public passenger vehicles in Pucakwangi, Jakenan, Winong Districts and their impact on community economic development. This research uses qualitative research techniques that combine range analysis and linear regression analysis. Based on the survey results, accessibility in Pucakwangi District is classified as low and access to public transportation is not smooth, while accessibility in Jakenan District is classified as moderate and access to public transportation is smooth, while in Winong District access is good and access to public transportation is very smooth. Accessibility has a significant influence on the economic development of residents in Winong District, while accessibility has a less significant influence on the economic development of residents in Pucakwangi District. This situation is not only caused by steep terrain and damaged roads, but also by the large number of vehicles and inappropriate conditions which have an impact on the smooth transactions of agricultural.